2011
DOI: 10.1111/j.1398-9995.2010.02533.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergy gap between Finnish and Russian Karelia on increase

Abstract: Disparities in the prevalence of atopy and atopic disease between Finnish and Russian Karelia have further grown. The 'allergy epidemic' continues in Finland and is mainly attributable to the years of birth effect shown in atopy prevalence. In Russia, no signs of the epidemic are discernible, although the decrease in total IgE may indicate a change in environmental exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 22 publications
3
56
0
1
Order By: Relevance
“…Almost all subjects (99.8%) were born before 1991, i.e. under Soviet conditions, and were, thus, exposed in their first years of life, and for a large majority throughout their childhood, to an environment and lifestyle likely to be protective against the development of allergic diseases in childhood and potentially later in life [9][10][11]13]. In studies conducted in children, wheezing was less associated with atopy in Estonia and in Russian Karelia compared with Sweden or Finland [9,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Almost all subjects (99.8%) were born before 1991, i.e. under Soviet conditions, and were, thus, exposed in their first years of life, and for a large majority throughout their childhood, to an environment and lifestyle likely to be protective against the development of allergic diseases in childhood and potentially later in life [9][10][11]13]. In studies conducted in children, wheezing was less associated with atopy in Estonia and in Russian Karelia compared with Sweden or Finland [9,33].…”
Section: Discussionmentioning
confidence: 99%
“…As in other eastern European countries that were formerly part of the Soviet Union [9,10], a lower prevalence of atopy and asthma was observed in Estonia compared with western Europe in the 1990s [11,12]. The degree of westernisation, and associated environmental and lifestyle-related exposures [9][10][11]13] were suggested to explain these differences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both self-reported asthma and allergic symptoms and objective markers of sensitisation were two to three times more common among the adults in North Karelia in Finland compared with Russian Karelia [7]. Re-examination of the same adult population 10 years later in 2007 revealed that the prevalence of symptoms and sensitisation had increased on the Finnish side but not on the Russian side [8]. The observed difference in the prevalence of allergic disorders between East and West Germany, Estonia and Sweden, and urban and rural Mongolia have provided somewhat comparable research opportunities and the results of these studies have been in line with the results of the Karelian Allergy Study [9][10][11].…”
mentioning
confidence: 99%
“…According to the European Federation of Allergy and Airway Diseases Patients Associations, 80 million (24.4 %) adults living in Europe are allergic. The allergy prevalence in children is 30-40 % and increasing (Laatikainen et al, 2011;Rönmark et al, 2009). Allergy to various types of pollen in the air, exacerbated by co-exposure to chemical pollutants and fine aerosols, is the number one chronic disease in Europe, overshadowing allergy to house dust mite and affecting over 20 % of the population (Bousquet et al, 2007).…”
Section: Introductionmentioning
confidence: 99%